Negative electrode for lithium metal secondary battery, method for producing same, and lithium metal secondary battery
By forming a concave and convex shape on the surface of the lithium metal layer and covering an antioxidant coating, the problem of improving the discharge capacity and rate characteristics of lithium metal secondary batteries is solved, and higher chemical stability and battery performance are achieved.
Patent Information
- Application Number
- CN202410793146.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-06-19
- Publication Date
- 2024-12-31
AI Technical Summary
The discharge capacity, rate characteristics and cycle characteristics of lithium metal secondary batteries are difficult to improve, and the surface area of the lithium layer is easily oxidized and the resistance increases and the characteristics decrease.
By forming a concave-convex shape on the surface of the lithium metal layer, the surface area is increased, and covered with an antioxidant coating film, a stable lithium carbonate coating film is intervened with a solvent of ether bonds or carbonate bonds, thereby improving chemical stability.
The negative electrode of lithium metal secondary battery with a large reaction area and chemically stable reaction area is realized, which improves the discharge capacity, rate characteristics and cycle characteristics, and extends the service life of the battery.
Smart Images

Figure CN119230742A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode for a lithium metal secondary battery and a method for manufacturing the negative electrode, and a lithium metal secondary battery. Background Art
[0002] In recent years, research and development of secondary batteries that help improve energy efficiency has been carried out to ensure that affordable, reliable, sustainable and advanced energy is available to many people. As a secondary battery, lithium metal secondary batteries that use lithium metal as a negative electrode active material have attracted attention due to their high energy density.
[0003] As a negative electrode of a lithium metal secondary battery, a laminated negative electrode is known, which includes a negative electrode collector and a lithium layer disposed on at least one surface of the negative electrode collector. In this laminated negative electrode, providing unevenness on the surface of the lithium layer has been studied (Patent Document 1).
[0004] [Prior Technical Literature]
[0005] (Patent Document)
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 7-272726 Summary of the invention
[0007] [Problems to be solved by the invention]
[0008] In addition, the problem of lithium metal secondary batteries is to improve discharge capacity, rate characteristics and cycle characteristics. In order to improve the discharge capacity and rate characteristics of lithium metal secondary batteries, it is effective to increase the surface area of the lithium layer of the negative electrode and expand the reaction area of the negative electrode. However, if the surface area of the lithium layer of the negative electrode is increased, the lithium layer is easily oxidized. If the lithium layer is oxidized, the surface resistance of the lithium layer will increase, and the characteristics such as discharge capacity, rate characteristics and cycle characteristics may decrease.
[0009] The purpose of this case is to provide a negative electrode for a lithium metal secondary battery with a large reaction area and chemical stability, a method for manufacturing the negative electrode, and a lithium metal secondary battery with improved discharge capacity, rate characteristics, and cycle characteristics, and to further contribute to energy efficiency.
[0010] [Technical means to solve the problem]
[0011] The present inventors have found that, in order to solve the above problems, it is effective to increase the surface area by making the surface of the lithium metal layer concavoconvex, and to cover the surface of the lithium metal layer with an anti-oxidation coating, thereby completing the present invention.
[0012] (1) A negative electrode for a lithium metal secondary battery, comprising a negative electrode collector and a lithium metal-containing layer disposed on at least one surface of the negative electrode collector, wherein at least a portion of the surface of the lithium metal-containing layer has a concave-convex shape, an expanded area ratio Sdr of the surface is greater than 1.0, and the surface is covered with an anti-oxidation coating.
[0013] According to the negative electrode for lithium metal secondary battery of (1), since at least a part of the surface of the lithium metal layer has a concave-convex shape, the development area ratio Sdr is greater than 1.0, so the surface area of the lithium metal layer, i.e., the reaction area, is large. In addition, since at least a part of the surface of the lithium metal layer is covered with an anti-oxidation coating, it is not easy to oxidize and is chemically stable.
[0014] (2) The negative electrode for a lithium metal secondary battery according to (1), wherein an arithmetic mean roughness Sa of the surface of the lithium metal-containing layer is 0.5 μm or more.
[0015] According to the negative electrode for lithium metal secondary battery of (2), since the arithmetic mean roughness Sa of the surface formed into a concavo-convex shape is large, the reaction area of the lithium metal layer is effectively increased. Since the arithmetic mean roughness Sa of the negative electrode for lithium metal secondary battery is large, the contact angle with respect to the electrolyte is small, so the wettability of the electrolyte is also improved.
[0016] (3) A negative electrode for a lithium metal secondary battery according to (1) or (2), wherein the antioxidant coating comprises oxygen and carbon, and the average content of the oxygen in the range from the surface of the antioxidant coating to a depth of 50 nm is greater than 3 and less than 5 in molar ratio relative to the average content of the carbon.
[0017] According to the negative electrode for lithium metal secondary battery of (3), since the anti-oxidation coating contains more than 3 moles and less than 5 moles of oxygen (O) relative to 1 mole of carbon (C), carbon and oxygen form carbonates, so it is chemically stable. In addition, since the thickness of the anti-oxidation coating is more than 50nm, the anti-oxidation ability is high. Therefore, the surface of the lithium metal layer is less prone to oxidation and is more chemically stable.
[0018] (4) The negative electrode for a lithium metal secondary battery according to any one of (1) to (3), wherein the antioxidant film comprises lithium carbonate.
[0019] According to the negative electrode for lithium metal secondary batteries of (4), since the anti-oxidation coating contains lithium carbonate, it is chemically more stable.
[0020] (5) The negative electrode for a lithium metal secondary battery according to any one of (1) to (4), wherein the content of silicon in the lithium metal-containing layer is 400 ppm by mass or less relative to the content of lithium in terms of mass ratio.
[0021] According to the negative electrode for lithium metal secondary battery of (5), since the silicon content is small, the stability becomes high and it is difficult to change with time.
[0022] (6) The negative electrode for a lithium metal secondary battery according to any one of (1) to (5), wherein a peel strength between the negative electrode current collector and the lithium metal-containing layer is 100 N / cm or more.
[0023] According to the negative electrode for lithium metal secondary battery of (6), the peel strength between the negative electrode current collector and the lithium metal containing layer is high, so the electrical characteristics are stable for a long period of time.
[0024] (7) A lithium metal secondary battery comprising the negative electrode for a lithium metal secondary battery according to any one of (1) to (6) above.
[0025] According to the lithium metal secondary battery of (7), since it has the above-mentioned negative electrode for lithium metal secondary batteries, the discharge capacity, rate characteristics and cycle characteristics are improved.
[0026] (8) A method for manufacturing a negative electrode for a lithium metal secondary battery, comprising: a preparation step of preparing a stack having a negative electrode collector and a lithium metal-containing layer arranged on at least one surface of the negative electrode collector; and a concave-convex transfer step of pressing a concave-convex transfer material having a concave-convex portion with an arithmetic mean roughness Sa of not less than 0.5 μm and an expanded area ratio Sdr of not less than 1.0 onto the surface of the stack on the side of the lithium metal-containing layer.
[0027] According to the method for manufacturing a negative electrode for a lithium metal secondary battery of (8), since a concave-convex transfer material having a concave-convex portion with a larger development area ratio Sdr is pressed against the lithium metal containing layer in the concave-convex transfer step, a concave-convex shape can be stably formed on the surface of the lithium metal containing layer.
[0028] (9) A method for producing a negative electrode for a lithium metal secondary battery according to (8), wherein, in the concavo-convex transfer step, a solvent having an ether bond or a carbonate bond is interposed between the surface of the stack on the lithium metal layer side and the concavo-convex transfer material.
[0029] According to the method for manufacturing a negative electrode for a lithium metal secondary battery of (9), since the solvent intervenes between the lithium metal-containing layer and the concave-convex transfer material, it is easy to peel the lithium metal-containing layer from the concave-convex transfer material. In addition, since the solvent has an ether bond or a carbonate bond, when the concave-convex transfer material is pressed against the lithium metal-containing layer to expose new lithium metal, the lithium metal reacts with the solvent to easily generate lithium carbonate. Therefore, an anti-oxidation coating can be stably formed on the surface of the lithium metal-containing layer.
[0030] (10) The method for producing a negative electrode for a lithium metal secondary battery according to (8) or (9), wherein an arithmetic mean roughness Sa of the surface of the concavo-convex transfer material is 0.5 μm or more.
[0031] According to the method for producing a negative electrode for a lithium metal secondary battery of (10), since the arithmetic mean roughness Sa of the surface of the concavo-convex transfer material used in the concavo-convex transfer step is large, the concavo-convex shape can be formed more stably on the surface of the lithium metal containing layer.
[0032] (Effects of the Invention)
[0033] According to the present invention, a negative electrode for a lithium metal secondary battery having a large reaction area and being chemically stable and a method for manufacturing the same can be provided. In addition, according to the present invention, a lithium metal secondary battery having improved discharge capacity, rate characteristics and cycle characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 FIG. 1 is a cross-sectional view showing a lithium metal secondary battery according to one embodiment of the present invention.
[0035] Figure 2 This is a scanning electron microscope (SEM) photograph of a cross section of a negative electrode for a lithium metal secondary battery according to one embodiment of the present invention.
[0036] Figure 3 The diagram schematically shows an apparatus for producing a negative electrode for a lithium metal secondary battery to which the method for producing a negative electrode for a lithium metal secondary battery according to one embodiment of the present invention can be applied. DETAILED DESCRIPTION
[0037] Hereinafter, embodiments of the present invention will be described with reference to the drawings.
[0038] Figure 1 FIG. 1 is a cross-sectional view showing a lithium metal secondary battery according to one embodiment of the present invention. Figure 2 This is a cross-sectional SEM photograph of a negative electrode for a lithium metal secondary battery according to one embodiment of the present invention.
[0039] exist Figure 1 In the present invention, the lithium metal secondary battery 10 includes an electrode stack in which a negative electrode 20, a separator 30, and a positive electrode 40 are stacked in this order. The electrode stack is accommodated in an outer casing (not shown) together with an electrolyte solution (not shown).
[0040] The negative electrode 20 includes a negative electrode current collector 21 and a lithium-containing metal layer 22 disposed on at least one surface of the negative electrode current collector 21 .
[0041] As long as the negative electrode collector 21 has the function of collecting the negative electrode 20, it is not particularly limited, and a material used as a negative electrode collector of a general lithium metal secondary battery can be used. Examples of materials for the negative electrode collector 21 include copper (Cu), stainless steel (SUS), nickel (Ni), etc. Examples of the shape of the negative electrode collector 21 include foil, plate, etc. When the negative electrode collector 21 is in the form of a foil, the thickness of the negative electrode collector 21 can be in the range of 5.0 μm to 50.0 μm. The arithmetic mean roughness Sa of the lithium metal layer 22 side of the negative electrode collector 21 can be, for example, in the range of 0.2 μm to 2.0 μm. The maximum height Sz of the lithium metal layer 22 side of the negative electrode collector 21 can be, for example, 1 / 3 or more relative to the thickness, or in the range of 5.0 μm to 20.0 μm.
[0042] The lithium metal layer 22 has the function of making it easier to generate a lithium metal layer by allowing lithium ions removed from the positive electrode 40 to precipitate on the surface of the negative electrode 20 when the lithium metal secondary battery 10 is charged. When the lithium metal secondary battery 10 is discharged, the lithium in the lithium metal layer precipitated on the surface of the negative electrode 20 will dissolve in the electrolyte. Figure 2 As shown, at least a portion of the surface of the lithium-containing metal layer 22 on the opposite side of the negative electrode collector 21 has a concave-convex shape, and the developed area ratio Sdr of the surface is set to be greater than 1.0. The thickness of the lithium-containing metal layer 22 can be, for example, in the range of 5 μm or more and 50 μm or less. The developed area ratio Sdr of the surface of the lithium-containing metal layer 22 formed into a concave-convex shape can also be in the range of 1.1 or more and 3.0 or less. The arithmetic mean roughness Sa of the surface of the lithium-containing metal layer 22 formed into a concave-convex shape can be, for example, greater than 0.5 μm, or in the range of 1.0 μm or more and 2.0 μm or less. The maximum height Sz of the surface of the lithium-containing metal layer 22 formed into a concave-convex shape can be, for example, greater than 1 / 3 relative to the thickness, or in the range of 10.0 μm or more and 25.0 μm or less. The developed area ratio Sdr, the arithmetic mean roughness Sa and the maximum height Sz can be measured using a commercially available laser microscope.
[0043] The lithium-containing metal layer 22 is covered with an anti-oxidation film (not shown). The anti-oxidation film prevents oxidation of the lithium-containing metal layer 22. Thus, even if the lithium metal secondary battery 10 is repeatedly charged and discharged, the lithium-containing metal layer 22 is not easily oxidized.
[0044] The anti-oxidation coating may contain oxygen (O) and carbon (C), or lithium carbonate. The average content of oxygen (O) in the range from the surface of the anti-oxidation coating (the surface of the lithium metal layer 22) to a depth of 50 nm may be 3 or more and 5 or less in terms of molar ratio (O / C molar ratio) relative to the average content of carbon (C). The O / C molar ratio in the above range indicates that the anti-oxidation coating contains carbonate and its thickness is 50 nm or more. The O / C molar ratio can be confirmed, for example, using X-ray photoelectron spectroscopy (X-ray Photoelectron Spectroscopy, XPS).
[0045] The lithium-containing metal layer 22 contains lithium or a lithium alloy. The lithium alloy contains a metal that forms an alloy with lithium. Examples of metals that form an alloy with lithium include Mg, Au, Ag, In, Ge, Sn, Pb, Al, and Zn. The lithium-containing metal layer 22 may also contain inevitable impurities. Inevitable impurities are substances that are inevitably mixed in the raw materials or the manufacturing process. As an example of inevitable impurities, silicon can be cited. The mass ratio of the silicon content to the lithium content (Si / Li mass ratio) can be, for example, 400 mass ppm or less.
[0046] The negative electrode current collector 21 and the lithium-containing metal layer 22 may also be bonded with strong adhesion. The peel strength between the negative electrode current collector 21 and the lithium-containing metal layer 22 may be, for example, 100 N / cm or more, or 200 N / cm or more.
[0047] As long as the separator 30 can prevent the negative electrode 20 from contacting the positive electrode 40 and allow lithium ions to penetrate, there is no particular limitation, and a material used as a separator for a general lithium metal secondary battery can be used. As the separator 30, for example, a porous sheet or a non-woven sheet can be used. Examples of materials for porous sheets include polyolefins such as polyethylene and polypropylene, aromatic amides, polyimides, fluororesins, etc. Examples of materials for non-woven sheets include glass fibers, cellulose fibers, etc. In the separator 30, a ceramic coating can be applied to the surface opposite to the positive electrode 40. Examples of materials for the ceramic coating include aluminum oxide (Al2O3) and silicon oxide (SiO2). The thickness of the ceramic coating can be, for example, in the range of more than 2.0 μm and less than 5.0 μm. If the thickness of the ceramic coating is within the above range, the increase in the internal resistance value caused by the increase in the thickness of the separator 30 can be suppressed, while the thermal stability of the separator 30 can be improved.
[0048] The positive electrode 40 includes a positive electrode current collector 41 and a positive electrode active material layer 42 disposed on the surface of the positive electrode current collector 41 on the separator 30 side.
[0049] The positive electrode current collector 41 is not particularly limited as long as it has the function of collecting the positive electrode 40, and a material used as a positive electrode current collector of a general lithium metal secondary battery can be used. Examples of materials for the positive electrode current collector 41 include aluminum, aluminum alloys, stainless steel, nickel, iron, and titanium. In addition, examples of the shape of the positive electrode current collector 41 include foil, plate, and the like.
[0050] The positive electrode active material layer 42 contains at least one positive electrode active material. There is no particular limitation on the positive electrode active material, and materials used in the positive electrode layer of a general lithium metal secondary battery can be used. As the positive electrode active material, for example, a layered active material containing lithium, a spinel type active material, an olivine type active material, etc. can be used. Specific examples of positive electrode active materials include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), LiNi p Mn q Co r O2(p+q+r=1), LiNi p Al q Co r O2 (p + q + r = 1), lithium manganate (LiMn2O4), Li 1+x Mn 2-x-y Heterogeneous element substituted Li-Mn spinel, lithium titanate (oxide containing Li and Ti), lithium metal phosphate (LiMPO4, M is selected from at least one of Fe, Mn, Co and Ni) represented by MO4 (x+y=2, M is selected from at least one of Al, Mg, Co, Fe, Ni and Zn), etc.
[0051] The positive electrode active material layer 42 may also contain a conductive additive to improve conductivity. In addition, from the perspective of flexibility, a binder may also be contained. There is no particular limitation on the conductive additive and the binder, and the conductive additive and the binder used in the positive electrode layer of a general lithium metal secondary battery may be used.
[0052] The electrolyte solution includes an organic solvent and an electrolyte. As an organic solvent, for example, cyclic carbonates, chain carbonates, cyclic ethers, chain ethers, hydrofluoroethers, aromatic ethers, sulfones, cyclic esters, chain carboxylates, and nitriles can be used. Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate. Examples of chain carbonates include dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Examples of cyclic ethers include tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,3-dioxolane, and 4-methyl 1,3-dioxolane. Examples of chain ethers include 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, and diethyl ether. Examples of hydrofluoroethers include 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl)ether, and 1,2-bis(1,1,2,2-tetrafluoroethoxy)ethane. Examples of aromatic ethers include anisole. Examples of sulfones include cyclopentane sulfone and methylcyclopentane sulfone. Examples of cyclic esters include γ-butyrolactone. Examples of chain carboxylates include acetate, butyrate, and propionate. Examples of nitriles include acetonitrile and propionitrile. The organic solvent may be used alone or in combination of two or more.
[0053] The electrolyte is a source of lithium ions that serve as a charge transfer medium and includes lithium salts. Examples of lithium salts include LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(CF3SO2)3, LiN(CF3SO2)2(LiTFSI), LiN(FSO2)2(LiFSI), and LiBC4O8. Lithium salts can be used alone or in combination of two or more. The concentration of the electrolyte is, for example, in the range of 1.5 to 4.0 mol / L.
[0054] According to the lithium metal secondary battery 10 of the present embodiment formed as the above structure, at least a portion of the surface of the lithium metal layer 22 of the negative electrode 20 has a concave-convex shape, and the development area ratio Sdr is greater than 1.0, and the surface area, i.e., the reaction area, of the lithium metal layer 22 is large. In addition, at least a portion of the surface of the lithium metal layer 22 is covered with an anti-oxidation coating, so the lithium metal layer 22 is not easily oxidized and is chemically stable. Therefore, when the lithium metal secondary battery 10 is charged, lithium is easily precipitated uniformly on the surface of the lithium metal layer 22, and when it is discharged, the precipitated lithium is easily dissolved uniformly. As a result, the discharge capacity, rate characteristics, and cycle characteristics of the lithium metal secondary battery 10 are improved.
[0055] In the lithium metal secondary battery 10 of the present embodiment, when the arithmetic mean roughness Sa of the lithium metal layer 22 is greater than 0.5 μm, the reaction area of the lithium metal layer 22 is substantially increased, so the discharge capacity and rate characteristics of the lithium metal secondary battery 10 are further improved. In addition, since the arithmetic mean roughness Sa of the lithium metal layer 22 is large, the contact angle with respect to the electrolyte is small, so the wettability of the electrolyte is also improved.
[0056] In the lithium metal secondary battery 10 of the present embodiment, when the average content of oxygen (O) in the range from the surface of the anti-oxidation film (the surface of the lithium metal layer 22) to a depth of 50 nm is greater than 3 and less than 5 relative to the average content of carbon (C) in terms of a molar ratio (O / C molar ratio), the anti-oxidation film contains more than 3 moles and less than 5 moles of oxygen (O) relative to 1 mole of carbon (C), and carbon and oxygen form carbonates, so it is chemically stable. In addition, the thickness of the anti-oxidation film is more than 50 nm, so the antioxidant capacity is high. Therefore, the surface of the lithium metal layer 22 is less prone to oxidation and is more chemically stable. As a result, the cycle characteristics of the lithium metal secondary battery 10 are further improved. In addition, when the anti-oxidation film contains lithium carbonate, it is further chemically stable. As a result, the cycle characteristics of the lithium metal secondary battery 10 are further improved.
[0057] In the lithium metal secondary battery 10 of the present embodiment, when the silicon content of the lithium metal layer 22 is as low as 400 mass ppm or less relative to the lithium content in terms of mass ratio, the stability of the lithium metal layer 22 becomes high and is less likely to change over time. As a result, the cycle characteristics of the lithium metal secondary battery 10 are further improved.
[0058] In the lithium metal secondary battery 10 of this embodiment, when the peel strength between the negative electrode current collector 21 and the lithium metal containing layer 22 is as high as 100 N / cm or more, the electrical characteristics are stable for a long period of time. Thus, the cycle characteristics of the lithium metal secondary battery 10 are further improved.
[0059] Next, a method for producing the negative electrode 20 for a lithium metal secondary battery will be described. Figure 3 Schematic diagram of a lithium metal secondary battery negative electrode manufacturing apparatus that can use the lithium metal secondary battery negative electrode manufacturing method according to one embodiment of the present invention. Figure 3As shown, the manufacturing device 100 has a pair of roller presses 110 and a concavo-convex forming stack 120. The concavo-convex forming stack 120 includes a negative electrode material stack 20a and a concavo-convex transfer material 122 arranged between a pair of demolding plates 121. The negative electrode material stack 20a has a negative electrode collector 21a and a lithium-containing metal layer 22a arranged on one surface of the negative electrode collector 21a. The concavo-convex transfer material 122 has a concavo-convex portion on one surface, and is arranged in a manner that the lithium-containing metal layer 22a contacts the concavo-convex portion of the concavo-convex transfer material 122. The developed area ratio Sdr of the concavo-convex portion of the concavo-convex transfer material 122 is set to be greater than 1.0. The developed area ratio Sdr of the concavo-convex portion of the concavo-convex transfer material 122 can also be in the range of greater than 1.1 and less than 3.0. The arithmetic mean roughness Sa of the concavoconvex part of the concavoconvex transfer material 122 may be, for example, 0.5 μm or more, or may be in the range of 1.0 μm or more and 2.0 μm or less. The maximum height Sz of the concavoconvex part of the concavoconvex transfer material 122 may be, for example, in the range of 5.0 μm or more and 25.0 μm or less. As the demolding plate 121, for example, a copper plate may be used.
[0060] The negative electrode 20 for a lithium metal secondary battery can be manufactured, for example, by a method including a preparation step and a concavo-convex transfer step.
[0061] The preparation step is a step of preparing the negative electrode material stack 20a. The negative electrode material stack 20a can be produced by, for example, superimposing the negative electrode collector 21a and the lithium-containing metal layer 22a and pressing them.
[0062] The concavoconvex transfer process is a process of preparing a concavoconvex forming laminate 120, and pressing the concavoconvex forming laminate 120 using a roller press 110 to press the concavoconvex transfer material 122 onto the surface of the lithium-containing metal layer 22a. By pressing the concavoconvex transfer material 122 onto the surface of the lithium-containing metal layer 22a, the concavoconvex shape of the concavoconvex portion of the concavoconvex transfer material 122 is transferred onto the surface of the lithium-containing metal layer 22a. The pressing conditions are not particularly limited, and are conditions such that the compression rate of the concavoconvex forming laminate 120 obtained by pressing is, for example, within a range of 30% to 50%. If the compression rate is within this range, it is easy to transfer the concavoconvex shape to the surface of the lithium-containing metal layer 22a without peeling the lithium-containing metal layer 22a from the negative electrode collector 21a. The compression rate of the lithium-containing metal layer 22a can be adjusted by adjusting the interval between a pair of roller presses 110 (in Figure 3 Indicated by arrows in the figure) to adjust.
[0063] In the concavo-convex transfer process, before the concavo-convex transfer material 122 is pressed onto the surface of the lithium-containing metal layer 22a, a solvent may be interposed between the lithium-containing metal layer 22a and the concavo-convex transfer material 122. The solvent may be a substance having an ether bond or a carbonate bond. As a solvent having an ether bond, for example, 1,2-dimethoxyethane (DME) may be used. As a solvent having a carbonate bond, for example, dimethyl carbonate may be used.
[0064] According to the manufacturing method of the negative electrode 20 for a lithium metal secondary battery of this embodiment formed as above, since the convex-concave transfer material 122 with a larger development area than Sdr is pressed against the lithium metal-containing layer 22a in the convex-concave transfer process, a convex-concave shape can be stably formed on the surface of the lithium metal-containing layer 22a.
[0065] In the manufacturing method of the negative electrode 20 for the lithium metal secondary battery of the present embodiment, when a solvent having an ether bond or a carbonate bond is interposed between the lithium metal-containing layer 22a and the concave-convex transfer material 122, it is easy to peel off the lithium metal-containing layer 22a and the concave-convex transfer material 122 after the concave-convex shape is formed. Furthermore, since the solvent has an ether bond or a carbonate bond, when the new lithium metal is exposed by pressing the concave-convex transfer material 122 onto the lithium metal-containing layer 22a, the lithium metal reacts with the solvent and easily generates lithium carbonate. Therefore, an anti-oxidation coating can be stably formed on the surface of the lithium metal-containing layer 22a after the concave-convex shape is formed. In addition, in the manufacturing method of the negative electrode 20 for the lithium metal secondary battery of the present embodiment, when the arithmetic mean roughness Sa of the surface of the concave-convex transfer material 122 is greater than 1.0 μm, the concave-convex shape can be more stably formed on the surface of the lithium metal-containing layer.
[0066] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment.
[0067] For example, the lithium metal secondary battery 10 of this embodiment is a non-aqueous solvent type lithium metal secondary battery containing an electrolyte solution, but the present invention is not limited thereto. The lithium metal secondary battery of the present invention may also be a solid electrolyte type lithium metal secondary battery.
[0068] In the manufacturing method of the negative electrode 20 for the lithium metal secondary battery of the present embodiment, a solvent having an ether bond or a carbonate bond is interposed between the lithium-containing metal layer 22a and the concave-convex transfer material 122, but it is not limited to this. Among them, when a solvent without an ether bond or a carbonate bond is used, it is preferably provided with the following steps: an antioxidant coating is formed on the surface of the lithium-containing metal layer 22a after the concave-convex shape is formed. As a method for forming an antioxidant coating, for example, a method of contacting the surface of the lithium-containing metal layer 22a after the concave-convex shape is formed with carbon dioxide can be used. In addition, in the manufacturing method of the negative electrode 20 for the lithium metal secondary battery of the present embodiment, a roller press 110 is used as a pressing device for the concave-convex forming stack 120, but the pressing device is not limited to this.
[0069] [Example]
[0070] In the present embodiment, as the raw material of the negative electrode, a Li-Cu stack formed by configuring Li foil on the surface of the Cu foil is used. As the Li-Cu stack, the two stacks of Li-Cu stacks 1 and 2 are used. The thickness of the Cu foil, the arithmetic mean roughness Sa and the maximum height Sz of the Li-Cu stacks 1 and 2 used in the present embodiment, the thickness of the Li foil, the arithmetic mean roughness Sa, the maximum height Sz and the development area ratio Sdr, and the Li-Cu interface peeling strength are shown in Table 1 below. The arithmetic mean roughness Sa and the maximum height Sz of the Cu foil are the values of the face on the Li foil side. The arithmetic mean roughness Sa, the maximum height Sz and the development area ratio Sdr of the Li foil are the values of the face on the opposite side of the Cu foil side. In addition, in the present embodiment, the arithmetic mean roughness Sa, the maximum height Sz and the development area ratio Sdr are measured using a laser microscope (VK-X3000, manufactured by KEYENCE Co., Ltd.).
[0071] [Table 1]
[0072]
[0073]
[0074] In this embodiment, three concavo-convex transfer materials 1 to 3 are used as concavo-convex transfer materials. The arithmetic mean roughness Sa, maximum height Sz thickness, and development area ratio Sdr of the concavo-convex transfer materials 1 to 3 used in this embodiment are shown in the following Table 2. The concavo-convex transfer materials 1 to 3 are all made of electrolytic nickel foil.
[0075] [Table 2]
[0076]
[0077] (Example 1)
[0078] DME (1,2-dimethoxyethane) is dripped on the surface of the Li layer of the Li-Cu stack 1. Subsequently, the surface of the Li layer of the Li-Cu stack 1 is overlapped with the concavoconvex part of the concavoconvex transfer material 2, and is clamped with a demolding copper foil having a thickness of 20 μm, thereby obtaining a concavoconvex forming stack stacked in sequence with a demolding copper foil, a Li-Cu stack 1, a concavoconvex transfer material 2, and a demolding copper foil. The obtained concavoconvex forming stack is pressurized with a linear pressure of 1 t / cm using a roller press in a manner such that the compression rate becomes 45%. The demolding copper foil and the concavoconvex transfer material 2 are peeled off from the pressurized concavoconvex forming stack to obtain a Li-Cu stack with concavoconvexity transferred on the surface of the Li layer.
[0079] (Examples 2 to 4, Comparative Examples 1 to 2)
[0080] A Li-Cu stack with projections and depressions was obtained in the same manner as in Example 1 except that the type of Li-Cu stack, the type of solvent added dropwise to the surface of the Li layer of the Li-Cu stack, the type of projection and depression transfer material, and the compression rate were changed as described in Table 3 below.
[0081] (Comparative Example 3)
[0082] The Li—Cu laminate 2 is used as the Li—Cu laminate of Comparative Example 3.
[0083] (Comparative Example 4)
[0084] The Li-Cu stack 2 is sandwiched with a demoulding copper foil to obtain a compression stack in which a demoulding copper foil, a Li-Cu stack 2, and a demoulding copper foil are sequentially stacked. The obtained compression stack is pressed with a linear pressure of 1 t / cm using a roller press so that the compression rate becomes 41%. When the demoulding copper foil is peeled off from the compressed stack after the compression, the Li foil is peeled off from the Cu foil of the Li-Cu stack 2.
[0085] (Comparative Example 5)
[0086] The Li—Cu laminate 1 was compressed in the same manner as in Comparative Example 4 except that the Li—Cu laminate 1 was used. The compressed Li—Cu laminate 1 was used as a Li—Cu laminate of Comparative Example 5.
[0087] [Table 3]
[0088]
[0089] [evaluate]
[0090] (1) Characteristics of Li layer in Li-Cu stack
[0091] For the Li-Cu stacks with unevenness obtained in Examples 1 to 4 and Comparative Examples 1 to 2, and the Li-Cu stacks of Comparative Examples 3 and 5, the arithmetic mean roughness Sa, maximum height Sz, development area ratio Sdr, O / C (oxygen / carbon) molar ratio, and Si / Li mass ratio of the Li layer were measured by the above-mentioned method. In addition, the arithmetic mean roughness Sa, maximum height Sz, and development area ratio Sdr were measured using a laser microscope (VK-X3000, manufactured by KEYENCE Co., Ltd.). The O / C (oxygen / carbon) molar ratio is the molar ratio of carbon (C) to oxygen (O) in the range from the surface of the Li foil to a depth of 50 nm using the XPS method. The Si / Li mass ratio is calculated based on the Si amount and Li amount of the Li-Cu stack with unevenness. The amount of Si and the amount of Li were obtained by dissolving the Li-Cu stack with irregularities with an acid and measuring the amount of Si and Li in the obtained solution using an inductively coupled plasma (ICP) emission spectrometer. The results are shown in Table 4 below.
[0092] (2) Characteristics of lithium metal secondary batteries
[0093] (positive electrode)
[0094] Acetylene black (AB) as an electronic conductive material, polyvinylidene fluoride (PVDF) as a binder (adhesive), and polyvinylpyrrolidone (PVP) as a dispersant were pre-mixed in N-methyl-2-pyrrolidone (NMP) as a dispersing solvent, and wet mixed with a rotary mixer to obtain a pre-mixed slurry. Then, Li1Ni 0.8 Co 0.1 Mn 0.1 O2 (NCM811) is mixed with the obtained premixed slurry, and a planetary mixer is used for dispersion treatment to obtain a positive electrode paste. The median particle size of NCM811 is 12 μm. Next, the obtained positive electrode paste is applied to an aluminum positive electrode collector without a primer layer, and dried, and after being pressed with a roller press, it is dried in a vacuum at 120°C to form a positive electrode plate having a positive electrode active material layer. The obtained positive electrode plate is punched into a size of 30 mm × 40 mm to form a positive electrode.
[0095] (Diaphragm)
[0096] The resin portion is a separator made of polyethylene (PE) with a thickness of 10 μm and a porosity of 45%, and a ceramic coating of 4 μm applied on the surface facing the positive electrode.
[0097] (Electrolyte)
[0098] A solution prepared by dissolving LiFSI [lithium bis(fluorosulfonyl)imide] in DME (1,2-dimethoxyethane) at a concentration of 2.5 mol / L was used.
[0099] (Manufacturing of lithium metal secondary batteries)
[0100] The above-mentioned separator and the above-mentioned positive electrode were sequentially stacked on the Li layer of the Li-Cu stack obtained in Examples 1 to 4 and Comparative Examples 1 to 2, and Comparative Examples 3 and 5 to obtain an electrode stack. The obtained electrode stack and the above-mentioned electrolyte were accommodated in an outer casing, and the outer casing was sealed to produce a lithium metal secondary battery.
[0101] (Chemical conversion process of lithium metal secondary battery)
[0102] The prepared lithium metal secondary battery was kept at a holding pressure of 50 kPa and allowed to stand at a temperature (25°C) for 24 hours. Subsequently, it was charged to 4.3 V at a constant current of 2.2 mA, then charged to 4.3 V at a constant voltage of 1 hour, allowed to stand for 30 minutes, and then discharged to 2.65 V at a constant current of 44 mA. This charge and discharge cycle was repeated 3 times.
[0103] (Initial discharge capacity)
[0104] The lithium metal secondary battery after the chemical conversion process was left to stand at a pressure of 0.8MPa and a temperature (25°C) for 1 hour. Subsequently, it was charged to 4.3V at a constant current of 14.5mA, and then charged to a constant voltage of 4.3V for 1 hour. After standing for 30 minutes, it was discharged to 2.65V at a current value of 14.5mA, and the discharge capacity at this time was taken as the initial discharge capacity (mAh). The results are shown in Table 4. In addition, below, for the initial discharge capacity obtained, the current value that can be discharged in 1 hour is set to 1C.
[0105] (Initial internal resistance value)
[0106] After the initial discharge capacity is measured, the lithium metal secondary battery is left to stand at a temperature (25°C) for 1 hour, and then charged at 0.2C. After the charging level [State of Charge (SOC)] is adjusted to 50%, it is left to stand for 10 minutes. Next, the C rate is set to 0.5C for a 10-second pulse discharge, and the voltage at the time of discharge for 10 seconds is measured. Then, the voltage at the time of discharge for 10 seconds relative to the current at 0.5C is plotted with the horizontal axis as the current value and the vertical axis as the voltage. Then, after standing for 10 minutes, supplementary charging is performed to restore the SOC to 50%, and then it is further left to stand for 10 minutes. The above operation is performed for each C rate of 1.0C, 1.5C, 2.0C, 2.5C, and 3.0C, and the voltage at the time of discharge for 10 seconds relative to the current value at each C rate is plotted. Then, the slope of the approximate straight line based on the least square method obtained from each plotted graph is used as the internal resistance value (Ω·cm 2 ). The results are shown in Table 4.
[0107] (High rate charge and discharge cycle test)
[0108] The battery was charged at 74 mA to 3.823 V, then at 52 mA to 4.051 V. It was then charged at 46 mA to 4.173 V, then at 22 mA to 4.3 V. It was then charged at 4.3 V at a constant voltage (CV) for 90 minutes.
[0109] The discharge was performed at a current value of 18 mA with constant current discharge until the voltage reached 2.65 V. This was repeated 48 times. The discharge capacity of the second cycle, the discharge capacity of the 48th cycle, and the ratio of the discharge capacity of the 48th cycle to the discharge capacity of the second cycle (discharge capacity retention rate) are shown in Table 4.
[0110] (Internal resistance value after cycle test)
[0111] The lithium metal secondary battery after the above-mentioned high-rate charge and discharge cycle test was subjected to the following operation for 2 cycles: constant current charging to 4.3V at 14.5mA, followed by constant voltage charging at a voltage of 4.3V for 1 hour, standing for 30 minutes, and then constant current discharge to 2.65V at a current value of 14.5mA. For the lithium metal secondary battery after 2 cycles, the internal resistance value was measured in the same manner as the above-mentioned initial internal resistance value. The internal resistance value obtained was used as the internal resistance value after the cycle test, and the ratio (variability) of the internal resistance value after the cycle test to the initial internal resistance value was calculated. The results are shown in Table 4.
[0112] [Table 4]
[0113]
[0114] In the lithium metal secondary battery using the Li-Cu laminate with concavoconvex obtained in Examples 1 to 4 as the negative electrode, the discharge capacity and discharge capacity retention rate of the 48th cycle of the high rate charge and discharge cycle test are high, and the change rate of the internal resistance value caused by the high rate charge and discharge cycle test is small. From this result, it can be seen that the lithium metal secondary battery using the Li-Cu laminate with concavoconvex obtained in Examples 1 to 4 as the negative electrode has a high capacity and excellent rate characteristics and cycle characteristics. In contrast, in the lithium metal secondary battery using the Li-Cu laminate with concavoconvex of Comparative Examples 1 to 2 and the Li-Cu laminate of Comparative Example 3, the discharge capacity and discharge capacity retention rate of the 48th cycle of the high rate charge and discharge cycle test are low, and the change rate of the internal resistance value caused by the high rate charge and discharge cycle test is large. It is believed that the poor characteristics of the high rate charge and discharge cycle test of Comparative Example 1 are because the development area of the Li-Cu laminate with concavoconvex of Comparative Example 1 is smaller than Sdr, and the reaction area is narrow. It is believed that the poor characteristics of the high-rate charge-discharge cycle test of Comparative Example 2 are because the O / C molar ratio of the Li-Cu stack with unevenness in Comparative Example 2 is large, so the surface is oxidized to generate components such as LiOH and Li2O, and it is not easy to precipitate lithium ions evenly during charging. It is believed that the poor characteristics of the high-rate charge-discharge cycle test of Comparative Example 3 are because the Li-Cu stack of Comparative Example 3 does not form unevenness on the surface and the reaction area is narrow. Comparative Example 5 failed to charge to 4.3V in the chemical conversion process of the lithium metal secondary battery. It is believed that this is because the surface of the Li layer of the Li-Cu stack of Comparative Example 5 does not form an uneven shape and the O / C molar ratio is large, so lithium ions are unevenly precipitated during charging, and an internal short circuit occurs.
[0115] Reference numerals
[0116] 10Lithium metal secondary battery
[0117] 20 negative electrode
[0118] 20a Negative electrode material stack
[0119] 21.21a Negative electrode collector
[0120] 22. 22a Lithium metal layer
[0121] 30 Diaphragm
[0122] 40 positive electrode
[0123] 41 positive electrode collector
[0124] 42Positive electrode active material layer
[0125] 100 Manufacturing Devices
[0126] 110 Roller Press
[0127] 120 Concavoconvex forming laminate
[0128] 121 demoulding plate
[0129] 122 Concave and convex transfer material
Claims
1. A negative electrode for a lithium metal secondary battery, comprising a negative electrode current collector and a lithium metal layer disposed on at least one surface of the negative electrode current collector, At least a portion of the surface of the lithium-containing metal layer has a concavo-convex shape, a developed area ratio Sdr of the surface is 1.0 or more, and the surface is covered with an anti-oxidation film.
2. The negative electrode for a lithium metal secondary battery according to claim 1, wherein The surface of the lithium-containing metal layer has an arithmetic mean roughness Sa of 0.5 μm or more.
3. The negative electrode for a lithium metal secondary battery according to claim 1, wherein The anti-oxidation film contains oxygen and carbon, and the average content of the oxygen in the range from the surface of the anti-oxidation film to a depth of 50 nm is 3 or more and 5 or less in molar ratio to the average content of the carbon.
4. The negative electrode for a lithium metal secondary battery according to claim 1, wherein The anti-oxidation film contains lithium carbonate.
5. The negative electrode for a lithium metal secondary battery according to claim 1, wherein The lithium-containing metal layer has a silicon content of 400 mass ppm or less relative to a lithium content in terms of mass ratio.
6. The negative electrode for a lithium metal secondary battery according to claim 1, wherein The peel strength between the negative electrode current collector and the lithium-containing metal layer is 100 N / cm or more. 7 . A lithium metal secondary battery comprising the negative electrode for a lithium metal secondary battery according to claim 1 .
8. A method for manufacturing a negative electrode for a lithium metal secondary battery, comprising: A preparation step of preparing a laminate having a negative electrode current collector and a lithium-containing metal layer disposed on at least one surface of the negative electrode current collector; and, In the concavo-convex transfer step, a concavo-convex transfer material having concavo-convex portions with a developed area ratio Sdr of 1.0 or more is pressed against a surface of the stacked body on the lithium metal layer side.
9. The method for producing a negative electrode for a lithium metal secondary battery according to claim 8, wherein: In the concavo-convex transfer step, a solvent having an ether bond or a carbonate bond is interposed between the surface of the laminate on the lithium metal layer side and the concavo-convex transfer material.
10. The method for producing a negative electrode for a lithium metal secondary battery according to claim 8, wherein: The arithmetic mean roughness Sa of the surface of the concavo-convex transfer material is 0.5 μm or more.
Citation Information
Patent Citations
Manufacture of metallic current collector
JP1995272726A
